Cruise infrastructure development in Auckland, New Zealand: a media discourse analysis (2008–2016). Issue 6 (3rd June 2017) - London, Wendy R.; Moyle, Brent D.; Lohmann, Gui
ABSTRACT: The deployment of mega cruise ships is putting pressure on ports to redesign or construct new infrastructure. However, there is limited research which considers the media discourse surrounding this development over a longitudinal period. The aim of this paper is to explore how the media portrays the cruise infrastructure debate in the complex and highly contested political environment of Auckland, New Zealand. Thematic analysis was used to determine the most salient themes found in 103 published articles. Results revealed the media shaped the debate, focusing on a volatile political environment characterised by distrust, a lack of transparency and differing objectives among key stakeholders. An outcome of this research is a rich, in-depth case study of cruise infrastructure development presented through the lens of media discourse. Future research should focus on the perceptions of decision-makers, stakeholders and the community using hedging and framing to probe the media discourse surrounding cruise infrastructure development.